RISC V Based Reconfigurable Manager for Event Transmission in SpaceFibre Networks - Suvorova, Elena (2021 29th Conference of Open Innovations Association (FRUCT), 2021)
In many aerospace networks based on the SpaceFibre standard, there is a need to transfer information about events occurring in various network nodes (terminal nodes, routers) for processing to other nodes. For example, information about faults during operation should be transmitted to a node performing system administration functions. In different networks, the set of events, information about which must be transmitted, the level of criticality of events for the functioning of the system, may be different. The required transmission characteristics may also vary. The SpaceFibre standard includes several mechanisms for transferring information about events from sources (terminal nodes and routers) to handler nodes. Different characteristics can be achieved (guaranteed delivery, guaranteed delivery time, the ability to transfer additional parameters, network load) with using different mechanisms. When designing a specific network, the system developer should be able to determine for each terminal node and router which events should be transmitted for processing to remote nodes and using which mechanisms this should be done. Terminal nodes and routers are developed as universal devices (systems-on-a-chip), which should provide the ability to send information about various events using various mechanisms. However, there are usually limits on the time that elapses between the occurrence of an event and sending information about it. Implementation overheads (area) are generally tightly constrained. The article proposes approach to designing an reconfigurable Event transmitting manager based on the RISC V ISA. For the proposed variants of implementation, the achievable time characteristics and overhead costs are evaluated.